2007
DOI: 10.1021/ma0609578
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Poly(n-butyl acrylate)-block-poly(acrylic acid) Diblock Copolymers by ATRP and Their Micellization in Water

Abstract: Amphiphilic diblock copolymers, poly(n-butyl acrylate)-block-poly(acrylic acid) (PnBA-PAA), with narrow molecular weight distribution (PDI ≤ 1.07) were prepared by atom transfer radical polymerization (ATRP) of n-butyl acrylate and tert-butyl acrylate (tBA), followed by selective acidolysis of the PtBA block. These polymers possess a soft PnBA hydrophobic block with a constant chain length of 90−100 monomer units and pH- and ionic strength-sensitive hydrophilic PAA block with DPPAA = 33−300 AA monomer units. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
222
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 171 publications
(234 citation statements)
references
References 58 publications
8
222
1
3
Order By: Relevance
“…Hydrogels, i.e., weakly cross-linked hydrophilic polymers, obtained after copolymerization of polyethylene glycol (PEG) with methacrylic acid were recently demonstrated to be efficient absorbents of uranyl ions [2]. On the other hand, the ability of amphiphilic PMAA-based block copolymers to self-assemble and produce dynamic micelles sensitive to different stimuli was shown to highly depend on the balance between hydrophobic and hydrophilic segments [3][4][5][6]. Since the performance of such copolymer materials is closely associated to structurally related parameters, unambiguous characterization of their microstructure is a crucial analytical issue.…”
mentioning
confidence: 99%
“…Hydrogels, i.e., weakly cross-linked hydrophilic polymers, obtained after copolymerization of polyethylene glycol (PEG) with methacrylic acid were recently demonstrated to be efficient absorbents of uranyl ions [2]. On the other hand, the ability of amphiphilic PMAA-based block copolymers to self-assemble and produce dynamic micelles sensitive to different stimuli was shown to highly depend on the balance between hydrophobic and hydrophilic segments [3][4][5][6]. Since the performance of such copolymer materials is closely associated to structurally related parameters, unambiguous characterization of their microstructure is a crucial analytical issue.…”
mentioning
confidence: 99%
“…Because of the well-defined structures, amphiphilic ionic molecules (AIMs) are studied widely in the field of AIS. Various nanostructures are obtained by the self-assembly of AIMs and the relationship between the morphologies and parameters was discovered by theoretical studies [1][2][3][4][5][6][7][8]. AIMs are designed and fabricated to form various nanostructures such as helical fibres, nanotubes, nanospheres and so on [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…of triuoroacetic acid with respect to the tBA units according to a procedure known to preserve the PnBA groups. 18,19 We found that for the complete hydrolysis of PtBA, the reaction time (Table 1) has to be extended as compared to other reported protocols.…”
mentioning
confidence: 99%
“…18 Theoretical calculations show that the cmc values of PnBA-PAA block copolymers dramatically decrease with the increase of the molar mass of PnBA. 20 It is noteworthy that the micellization of such copolymers is considered to be a kinetically controlled process.…”
mentioning
confidence: 99%